Application Of Phase Change Materials (PCM’s) To Preserve The Freshness Of Seafood Products - Wiwik Pudjiastuti; Arie Listyarini; Arief Riyanto (Jurnal Kimia dan Kemasan, 2015)
The application of Phase Change Materials (PCMs) as one of latent heat energy storage materials in smart cold system has been investigated for preserving a freshness of seafood products. In this investigation, PCMs was installed on Expanded Polystyrene (EPS) box system as insulated container. The freshness of the seafood product was shown by the time of keeping temperature during storage or distribution. Keeping temperature time of smart cold system using PCMs was compared to conventional cold system using ice cubes. The result shows that EPS box system using PCMs can prolonged the keeping temperature time and reached colder temperature than the conventional one. Microbiology test of products was monitored to prove that products occured no changes in quality.